Comparison of concentrated separator byproduct and cane molasses for finishing heifers - Loe, E.R.; Kessen, T.J.; Montgomery, Sean P.; Pike, J.N.; Sindt, J.J.; Sulpizio, M.J.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We compared concentrated separator byproduct (CSB) to cane molasses on feedlot performance and carcass merit of 394 crossbred yearling beef heifers fed for 148 days. Sugar beet molasses undergoes a process in which approximately half of the sugar is removed, concentrating protein and mineral in CSB. Compared with cane molasses, CSB has more crude protein, ash, and moisture. Two diets based on steam-flaked corn containing either CSB or cane molasses at 5% (dry matter basis) of the diet were fed. Feedlot performance was similar between heifers fed the two diets (P>0.23). Apparent dietary concentrations of net energy for gain (NEg), calculated from performance, were similar (P=0.21) for the CSB and cane molasses diets. The apparent NEg for cane molasses and CSB were not statistically different (P=0.20); the NEg concentrations of cane molasses and CSB were 0.21 and 0.50 ± 0.15 Mcal/lb, respectively. Carcass characteristics were similar between diets. Based on our data, CSB and cane molasses have a similar feeding value and energy content in beef finishing diets that are based on steam-flaked corn.
Keywords: Beef; Concentrated separator byproduct (CSB); Cane molasses; Finishing heifers